An Update on Zoonotic Cryptosporidium Species and Genotypes in Humans - Una Ryan (MDPI AG, 2021)
The enteric parasite, Cryptosporidium is a major cause of diarrhoeal illness in humans and animals worldwide. No effective therapeutics or vaccines are available and therefore control is dependent on understanding transmission dynamics. The development of molecular detection and typing tools has resulted in the identification of a large number of cryptic species and genotypes and facilitated our understanding of their potential for zoonotic transmission. Of the 44 recognised Cryptosporidium species and >120 genotypes, 19 species, and four genotypes have been reported in humans with C. hominis, C. parvum, C. meleagridis, C. canis and C. felis being the most prevalent. The development of typing tools that are still lacking some zoonotic species and genotypes and more extensive molecular epidemiological studies in countries where the potential for transmission is highest are required to further our understanding of this important zoonotic pathogen. Similarly, whole-genome sequencing (WGS) and amplicon next-generation sequencing (NGS) are important for more accurately tracking transmission and understanding the mechanisms behind host specificity.